A tale of two villages: Isotopic insight into diet, economy, cultural diversity and agrarian communities in medieval (11th–15th century CE) Apulia, Southern Italy. (December 2019) - Rolandsen, Guro Linnerud; Arthur, Paul; Alexander, Michelle
Highlights: Bulk collagen δ 13 C and δ 15 N data from medieval humans and animals from Apulia, Italy. Results indicate dietary differences between sites and ethnic and age groups. Local agricultural practices were not affected by ruling regime. Provides new data for low socioeconomic and culturally diverse agrarian communities. Abstract: This study uses bulk stable isotope analysis of carbon (δ 13 C) and nitrogen (δ 15 N) of bone collagen to investigate the diets of two deserted medieval villages, Apigliano and Quattro Macine, in Apulia, Southern Italy. The sampled cemeteries represent Latin Catholic and Greek Orthodox religious culture. The aim was to investigate potential inter- and intra-site variation (age, sex, faith, ethnicity, burial location) between these culturally diverse populations and place them in a wider medieval Italian context. Bone collagen was analysed from 103 humans and 33 animals. Sixty-eight humans were sampled from Apigliano (c.13th–15th centuries AD) and 35 individuals from Quattro Macine (c.11th–15th centuries AD). Non-adults, and adults of male, female and unknown sex and contemporaneous animals were sampled from both sites. The isotopic data indicates that both sites subsisted on a terrestrial C3 -based diet with a limited intake of high trophic level protein from meat and fish, as indicated by low δ 15 N values. Diet of non-adults matched that of adults from five years of age at Apigliano, but Quattro Macine non-adults exhibit significantly depleted δ 15 N values. Variability in diet differed between the two settlements, with Apigliano demonstrating a greater range and higher δ 15 N values overall than Quattro Macine. We interpret the differential dietary patterning between sites as a result of socio-cultural and socio-economic factors. Comparison with isotopic data from other Medieval populations indicates trends in subsistence differences across the Italian Peninsula, particularly associated with the rural/urban nature of settlement and the local economy. This research adds new medieval dietary evidence from a geographical area previously unexplored using isotopic techniques.